Introducing criteria based audit into Ugandan maternity units. Issue 1 (2nd February 2004) - Weeks, A D; Alia, G; Ononge, S; Mutungi, A; Otolorin, E O; Mirembe, F M
Abstract : Problem: Maternal mortality in Uganda has remained unchanged at 500/100 000 over the past 10 years despite concerted efforts to improve the standard of maternity care. It is especially difficult to improve standards in rural areas, where there is little money for improvements. Furthermore, staff may be isolated, poorly paid, disempowered, lacking in morale, and have few skills to bring about change. Design: Training programme to introduce criteria based audit into rural Uganda. Setting: Makerere University Medical School, Mulago Hospital (large government teaching hospital in Kampala), and Mpigi District (rural area with 10 small health centres around a district hospital). Strategies for change: Didactic teaching about criteria based audit followed by practical work in own units, with ongoing support and follow up workshops. Effects of change: Improvements were seen in many standards of care. Staff showed universal enthusiasm for the training; many staff produced simple, cost-free improvements in their standard of care. Lessons learnt: Teaching of criteria based audit to those providing health care in developing countries can produce low cost improvements in the standards of care. Because the method is simple and can be used to provide improvements even without new funding, it has the potential to produce sustainable and cost effective changes in the standard of health care. Follow up is needed to prevent a waning of enthusiasm with time.